Enhanced network effects and stochastic modelling in generation expansion planning: Insights from an insular power system. (September 2020) - Fitiwi, Desta Z.; Lynch, Muireann; Bertsch, Valentin
Abstract: Electricity generation capacity expansion is driven by both economic and socio-political realities. Policy makers determine public infrastructural decisions, such as climate and renewable targets, and transmission infrastructure, and the optimal generation capacity expansion follows. Policy makers therefore require planning models that can determine the optimal generation capacity mix in the long run under various scenarios, including policy choices. This work presents a planning model based on linearised alternating current optimal power flow which determines optimal generation capacity expansion and operation, in a least-cost manner, given global and local technical constraints, as well as policy decisions. We apply the model to a test case of the island of Ireland, which has two weakly interconnected systems, high renewable generation targets and low storage and interconnection. We determine the optimal generation expansion and operation out to 2030 considering the effects of increased multi-area interconnection, existing fossil fuel generation phase-out and increased renewable generation targets and carbon prices. Our results find that costs and emissions are driven primarily by the decommissioning of old inefficient generation units. High renewable targets, on the other hand, render increased carbon prices relatively ineffective in reducing system emissions. Furthermore, high renewable generation targets crowd out low-carbon power generation options such as carbon capture and storage (CCS). The strategic north-south interconnection has little effect on renewable energy source installations required to achieve renewable power generation targets but does impact on security of supply and the congestion level across the island. Highlights: A decision support model for medium to long-term generation expansion planning. Insights from an Irish study on optimal generation expansion mix under various policy scenarios. Effects of multi-area interconnection, fossil fuel phase-out, RES-E targets and carbon prices. Costs and emissions driven primarily by decommissioning of old inefficient generation units. High renewable targets render increased carbon prices ineffective in reducing emissions.